Drivers and applications of integrated clean-up technologies for surfactant-enhanced remediation of environments contaminated with polycyclic aromatic hydrocarbons (PAHs). (June 2017) - Liang, Xujun; Guo, Chuling; Liao, Changjun; Liu, Shasha; Wick, Lukas Y.; Peng, Dan; Yi, Xiaoyun; Lu, Guining; Yin, Hua; Lin, Zhang; Dang, Zhi
Abstract: Surfactant-enhanced remediation (SER) is considered as a promising and efficient remediation approach. This review summarizes and discusses main drivers on the application of SER in removing polycyclic aromatic hydrocarbons (PAHs) from contaminated soil and water. The effect of PAH-PAH interactions on SER efficiency is, for the first time, illustrated in an SER review. Interactions between mixed PAHs could enhance, decrease, or have no impact on surfactants' solubilization power towards PAHs, thus affecting the optimal usage of surfactants for SER. Although SER can transfer PAHs from soil/non-aqueous phase liquids to the aqueous phase, the harmful impact of PAHs still exists. To decrease the level of PAHs in SER solutions, a series of SER-based integrated cleanup technologies have been developed including surfactant-enhanced bioremediation (SEBR), surfactant-enhanced phytoremediation (SEPR) and SER-advanced oxidation processes (SER-AOPs). In this review, the general considerations and corresponding applications of the integrated cleanup technologies are summarized and discussed. Compared with SER-AOPs, SEBR and SEPR need less operation cost, yet require more treatment time. To successfully achieve the field application of surfactant-based technologies, massive production of the cost-effective green surfactants (i.e. biosurfactants) and comprehensive evaluation of the drivers and the global cost of SER-based cleanup technologies need to be performed in the future. Graphical abstract: Highlights: Surfactant-based cleanup technologies (SER, SEBR, SEPR, and SER-AOPs) are reviewed. Drivers of different approaches in removing PAHs from soil/water are discussed. A review on the applications of SER-based integrated technologies is given. Toxicity of treated soil/water using the different processes should be assessed. Scaling up the SER-based technologies is needed to assess their cost and efficacy. Abstract : Surfactant-enhanced remediation (SER) and its integrated cleanup technologies are reviewed to provide general SER-based strategies for the remediation of PAHs-contaminated environments.